Time costs of children as parents' foregone leisure - Olivia Ekert-Jaffe; Shoshana Grossbard (Institute for the Study of Labor (IZA), 2011)
This article uses data from the 1998-1999 French INSEE time use survey to estimate the time costs of children. The focus is on couples with two spouses working Full-Time in the labor force in order to avoid issues of substitution between home production and labor supply. Time costs are computed in terms of hours of foregone leisure. The model accounts for selection into full-time employment and controls for use of hired childcare workers. We find that the foregone leisure cost of one child under age 3 is 1.9 hour for mothers and 2.2 hours for fathers. We find economies of scale for mothers but not for fathers. The presence of a childcare worker per child reduces the time cost of children to a couple of parents by 5%.
urn:nbn:de:101:1-201106202149
Keywords: J13; J22; 330; children; time costs; leisure